Effect of Institutional Pillars on Small and Micro Enterprises Firm Performance in Ethiopia - Mohammed, Endres Ahmed (International Review of Management and Marketing, 2020)
Though much research had been conducted examining the role of institutions on the practice of micro and small enterprise, it is now the effect of institutional pillars on organization performance is to be assessed in Ethiopian case. Examining the 200 small and micro enterprises (SME), we had tested a model of institutional variables to explain performance of firms. To cater the variance of firm performance due to the effect of institutional environment, we used structural equation modeling nesting polychoric correlation to measure firm performance measured in ordinal data variables. We found that the normative and cognitive institutional pillars positively correlated to firm performance, while the regulative pillar is negative but insignificant affecting performance. Thus, we showed that entrepreneurs’ interpretation of the value system within the society regarding innovation and their perception about innovation practice determines firm performance keeping the quality of idea and their resource endowment constant, in micro and small enterprise in Ethiopia. Keywords: Institutional theory, regulative, normative, cognitive pillar, firm performance. JEL Classifications: L3, L25, L26 DOI: https://doi.org/10.32479/irmm.9131